2014
DOI: 10.3390/molecules19067497
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Structure on the Interactions between Five Natural Antimicrobial Compounds and Phospholipids of Bacterial Cell Membrane on Model Monolayers

Abstract: Monolayers composed of bacterial phospholipids were used as model membranes to study interactions of the naturally occurring phenolic compounds 2,5-dihydroxybenzaldehyde and 2-hydroxy-5-methoxybenzaldehyde, and the plant essential oil compounds carvacrol, cinnamaldehyde, and geraniol, previously found to be active against both Gram-positive and Gram-negative pathogenic microorganisms. The lipid monolayers consist of 1,2-dihexadecanoyl-sn-glycero-3-phosphoethanolamine (DPPE), 1,2-dihexadecanoyl-sn-glycero-3-pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
59
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(64 citation statements)
references
References 43 publications
5
59
0
Order By: Relevance
“…On the one hand, a progressive reduction of the isotherm slope in the pressure range 15–45 mN/m was detected from BAL 2 to BAL 5, with respect to Curosurf and BAL 1 (Fig 6A). Considering that the isotherm slope in this pressure range is representative of the packing density of the phospholipid chains into the monolayer[33, 34], it seems that sequential BALs become gradually organized in more fluid films. On the other hand, the required spread volume of the samples to reach a surface pressure of 15 mN/m varied significantly (Fig 6B).…”
Section: Resultsmentioning
confidence: 99%
“…On the one hand, a progressive reduction of the isotherm slope in the pressure range 15–45 mN/m was detected from BAL 2 to BAL 5, with respect to Curosurf and BAL 1 (Fig 6A). Considering that the isotherm slope in this pressure range is representative of the packing density of the phospholipid chains into the monolayer[33, 34], it seems that sequential BALs become gradually organized in more fluid films. On the other hand, the required spread volume of the samples to reach a surface pressure of 15 mN/m varied significantly (Fig 6B).…”
Section: Resultsmentioning
confidence: 99%
“…Concerning geraniol, Nowotarska et al (2014) reported that this terpen was active against both Gram-positive and Gram-negative pathogenic microorganisms. Singh et al, 2002; found that geraniol-derived compounds showed very promising antimalarial in vivo activity against multidrug resistant Plasmodium yoelii.…”
Section: Discussionmentioning
confidence: 99%
“…3436 Similarly, dipalmitoylphosphatidylethanolamine (DPPE) is utilized to model the inner leaflet of bacterial and eukaryotic membranes for drug and lipid interactions. 3738 These two lipids have become a very appealing model interface to study drug and lipid interactions and therefore were used in this study as a model membrane interface to study the interactions of the N-containing compounds in Figure 1. 3436,3738 To determine the molecular-detail interactions of small aromatic N-containing compound with an interface, aerosol-OT (AOT) reverse micelles (RM) 3942 were examined.…”
Section: Introductionmentioning
confidence: 99%
“…3738 These two lipids have become a very appealing model interface to study drug and lipid interactions and therefore were used in this study as a model membrane interface to study the interactions of the N-containing compounds in Figure 1. 3436,3738 To determine the molecular-detail interactions of small aromatic N-containing compound with an interface, aerosol-OT (AOT) reverse micelles (RM) 3942 were examined. 30 · 43–47 RMs are self-assembled microemulsion that form at low water concentration.…”
Section: Introductionmentioning
confidence: 99%